(untitled) (Research, Society and Development, 2022)
To identify dietary patterns and assess their association with the presence or absence of type 1 diabetes (T1D) and biochemical markers of cardiovascular risk. The study involved patients with T1D and healthy individuals (n=90). Patients with T1D were recruited at the Endocrinology and Diabetes Outpatient Clinic of the Hospital from the Federal University of Ceará (HUWC-UFC) and healthy adult individuals were recruited at the State University of Ceará (UECE) and UFC, in the period from 2016 to 2017. Dietary intake was obtained through 24-hour recalls. Dietary patterns were identified by principal component factor analysis, followed by orthogonal varimax rotation. Poisson regression estimated the prevalence ratios of independent variables in relation to outcomes. Three main patterns were identified: prudent (poultry, fish, tame fruits, whole grains, vegetables, fruits, skimmed milk, and with a negative charge for beef, pork, cereal, legumes, and whole milk), snack (sandwich and fruit smoothie) and western (industrialized drinks, sweets, snacks, and foods rich in fats). Association was observed between prudent pattern with lower HDL cholesterol level; snack pattern with lower fasting blood glucose and higher triglyceride level and the western one with higher fasting blood glucose level. There was no association between patterns and the presence or absence of T1D. The patterns identified were not associated with the presence or absence of T1D, but have been related with HDL cholesterol, triglycerides, and blood glucose.